Implementation of Scout Training Activities in the Formation of Leadership Character For Grade 5 Students of Kulliyatul Mu’allimin Al-Islamiyah at Darussalam Gontor Modern Islamic Institution For Girls - Ahmad Hidayatullah Zarkasyi; Dwi Jayanti (At-Ta'dib, 2019)
Islamic education Institutions are very important for all students. Since how Indonesia looks can be seen in the existing education. Education must be returned to its original character, that is, to deliver students to be superior individuals in accordance with the realm of existing aspects, namely: psychomotor, cognitive and affective. This research aims at describing the implementation of training scout activities in the formation of leadership character for grade 5 and for describies, the supporting and inhibiting factors in the implementation of scout training activities in the formation of leadership character for grade 5 students. This type of research is descriptive qualitative research.  For data collection of this study the researcher used 3 instruments, namely interview, observation and documentation. This research used Miles and Huberman’s data analysis framework which included 3 steps. The results of the analysis found by the researcher with the existence of scout training activities such as scout training on Thursday, Akbar’s camp and ceremonies can add to the 5th grade for leadership character, disciplined and responsible for each event. One of the supporting factors is the large number of students who are very enthusiastic in participating in this scout traning activities and one of the inhibiting factors is the fact that scout training activities is held on the day of Thursday that day, in which many of students are tired of the intense extracurricular activities on Thursday.